2022
DOI: 10.1101/2022.09.04.22279567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic evidence for the link of misophonia with psychiatric disorders and personality

Abstract: Patients with misophonia experience strong negative emotional responses to human produced sounds at a level disrupting normal social interaction. The exact nature of the disorder remains a matter of debate. Here, we investigated the genetic aetiology of misophonia in order to understand contributing factors and shed light on the nosology of the disorder. For misophonia, we used an unpublished genome wide association study (GWAS) from 23andMe on a self-report item probing a common misophonic symptom: the occurr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…This is consistent with the findings of Andermane et al (2023) who showed that autistic traits were less associated with classical oronasal misophonic triggers and more with a general sensitivity to sounds. Our finding might also in part explain the discrepancy from a previous study where ASC was found to be genetically inversely correlated with rage misophonia (Smit et al, 2023).…”
Section: Discussioncontrasting
confidence: 91%
“…This is consistent with the findings of Andermane et al (2023) who showed that autistic traits were less associated with classical oronasal misophonic triggers and more with a general sensitivity to sounds. Our finding might also in part explain the discrepancy from a previous study where ASC was found to be genetically inversely correlated with rage misophonia (Smit et al, 2023).…”
Section: Discussioncontrasting
confidence: 91%